Differential loss of ancestral gene families as a source of genomic divergence in animals. - Hughes, Austin L (2004)
A phylogenetic approach was used to reconstruct the pattern of an apparent loss of 2106 ancestral gene families in four animal genomes (Caenorhabditis elegans, Drosophila melanogaster, human and fugu). Substantially higher rates of loss of ancestral gene families were found in the invertebrates than in the vertebrates. These results indicate that the differential loss of ancestral gene families can be a significant factor in the evolutionary diversification of organisms.